The Sanctity of Divine Symbols and Their Impact on the Reformation of Thought and Action - Dr. Abdul Qadoos; Dr. M. Shoaib Khan (Journal of Religion and Society, 2026)
Islam presents a complete and comprehensive way of life that guides every dimension of human existence. Its foundation rests on belief in Tawḥīd (the oneness of Allah), obedience to His commands, and adherence to the teachings of the Prophet Muhammad (peace be upon him). This guidance is not confined to theory; rather, it is manifested in practical life through what the Qur’an describes as the Shaʿāʾir Allāh (the Symbols of Allah). The Qur’an repeatedly emphasizes these symbols and declares their reverence a clear sign of true faith. Allah Almighty states: “Whoever honors the symbols of Allah, it is indeed from the piety of the hearts.” This highlights that respect for these symbols is not merely outward; it reflects an inner state of humility, submission, and consciousness of Allah (taqwā). In the contemporary Muslim world, one of the major causes of intellectual and moral decline is the weakening of this very spirit. Religious practices are often performed as formalities, while their deeper meanings and transformative impact are overlooked. As a result, both individual character and collective identity have been adversely affected. This study seeks to demonstrate that a proper understanding and sincere reverence for the symbols of Allah are essential for the reformation of thought and action. It argues that these symbols are not only expressions of faith but also powerful means of spiritual, moral, and social transformation. Keywords: Divine Symbols, Qur’an, Hadith, Sanctity, Thought, Action